(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study is an applied investigation on the challenges Indianunder GraduateCollege children in sixth grade face in the four language skills (“reading,” “writing,” “speaking,” and “listening”). It was determined that the most advanced students in the sample would be those in their last year of under GraduateCollege. It has been shown that the amount of time spent teaching English to Indianunder Graduates is inversely related to their performance on standardised tests. Although the English textbook for the introductory courses assumes a certain degree of proficiency in reading, writing, speaking, and listening, this negative connotation arises from the students’ demonstrable lack of these skills. The present study aims to shed light on the difficulties under GraduateIndian-preparatory children may have while writing essays, reading